Asymptotic Properties of Functionals of the Squared Periodograms for Stationary Random Fields - Lyudmyla Sakhno (Austrian Journal of Statistics)
The paper presents conditions for the asymptotic normality of functionals of squared periodograms based on tapered data. Stationary Gaussian random fields are considered. Two limit theorems are stated: for the first one the certain condition of integrability of the spectral density of the field is assumed, and the second result is for spectral densities with the prescribed behavior near the points of singularities.